Changes in Delivery Timing for High-Risk Pregnancies in the United States - Little, Sarah E.; Robinson, Julian N.; Zera, Chloe A. (American Journal of Perinatology, 2020)
Objective This study was aimed to assess whether the “39-week” rule is being extended to high-risk pregnancies and if so whether this has led to changes in neonatal morbidity or stillbirth.Study Design Birth certificate data between 2010 and 2014 from 23 states (55% of births in the United States) were used. Pregnancies were classified as high risk if they had any one of the following: maternal age greater than or equal to 40 years, prepregnancy body mass index (BMI) greater than or equal to 40 kg/m2, chronic (prepregnancy) hypertension, or diabetes (pregestational or gestational). Delivery timing changes for all pregnancies at term (37 weeks or greater) were compared with changes in the high-risk population. Neonatal morbidities (neonatal intensive care unit [NICU] admission, need for assisted ventilation, 5-minute Apgar score, and macrosomia), maternal morbidities (intensive care unit [ICU] admission, cesarean delivery, operative vaginal delivery, chorioamnionitis, and severe perineal laceration), and stillbirth rates were compared across time periods. Multivariate logistic regression was used to analyze whether gestational age–specific morbidity changes were due to shifts in delivery timing.Results For the overall population, there was a shift in delivery timing between 2010 and 2014, a 2.5% decrease in 38-week deliveries, and a 2.3% increase in 39-week deliveries (p < 0.01). This gestational age shift was identical in the high-risk population (2.7% decrease in 38-week deliveries and 2.9% increase in 39-week deliveries). For the high-risk population, NICU admission increased from 5.4 to 6.3% in 2014 (p < 0.01) and assisted ventilation rates declined from 3.8 to 2.9% (p < 0.01). These changes, however, were independent of changes in delivery timing. There was no increase in the rate of stillbirth (0.23% in 2010 and 0.23% in 2014; p = 0.50).Conclusion There was a significant shift in delivery timing for high-risk pregnancies in the United States between 2010 and 2014. This shift, however, did not result in statistically significant changes in either neonatal morbidity or stillbirth.Key Points
Keywords: 39-week rule; nonmedically indicated induction; elective induction; delivery timing